Study of emotional intelligence and students' adjustment to university among first year undergraduate students in Malaysia - Athirah, Ali Rahman (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study investigated the relationship between emotional intelligence and students‟ adjustment to university among first year undergraduate students in Malaysia. Besides that, this study also investigated the differences in adjustment to university and emotional intelligence by demographic factors respectively. Quantitative method and simple random sampling was utilized. Wong and Law Emotional Intelligence Scale (WLEIS) was used to measure the emotional intelligence of the students whereas College Adjustment Test (CAT) was used to measure the students‟ adjustment to university. Pearson Correlation was used to test the relationship between emotional intelligence and students‟ adjustment to university. Independent t-test was used to examine the differences in students‟ adjustment to university and emotional intelligence according to genders. Meanwhile, One Way ANOVA was used to examine the differences in students‟ adjustment to university and emotional intelligence according to ethnicity, programmes, family structure, and household incomes respectively. Overall, the research finding indicated there is indeed a significant relationship between emotional intelligence and students‟ adjustment to university. However, there were no significant differences were found in students‟ adjustment to university and emotional intelligence by demographic factors. Therefore, this study suggests that emotional intelligence plays an important role in the students‟ adjustment to university and needs to be emphasized and improved in educational institutions in order to improve students‟ adjustment to university simultaneously.